CT (Computed Tomography) visual nano particle based on amphiphilic block copolymer as well as preparation method and application of CT visual nano particle

By self-assembly encapsulating the iodine-containing monomer based on polyethylene glycol and silicone oxygen ether monomer to form nanoparticles, the problems of nephrotoxicity and short circulation half-life of existing CT contrast agents are solved, and the problem of The structural stability and good CT imaging effect of nanoparticles.

CN119463071AActive Publication Date: 2025-02-18SUN YAT SEN UNIV +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411450487.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-02-18
Estimated Expiration
2044-10-17

AI Technical Summary

Technical Problem

The existing organic small molecule CT contrast agents have problems such as nephrotoxicity, short circulation half-life and easy to cause immune responses, making it difficult to achieve long circulation, low toxicity and non-immunogenic effects.

Method used

By developing an amphiphilic block copolymer based on polyethylene glycol and silicone oxygen ether monomers, the copolymer is self-assembled and encapsulated in aqueous solution to form nanoparticles and achieve the content by adjusting pH. The hydrolytic cross-links the iodine monomer and the hydrophobic section of the copolymer to form structurally stable iodine-containing nanoparticles.

Benefits of technology

The iodine-containing nanoparticles produced have good CT imaging effects and biocompatibility, have longer cycle times and lower toxicity, and potentially become the next generation CT imaging contrast agent.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463071A_ABST
    Figure CN119463071A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of biological detection, and particularly relates to a CT (Computed Tomography) visual nano particle based on an amphiphilic block copolymer as well as a preparation method and application of the CT visual nano particle. The preparation method comprises the following steps: firstly, preparing an amphiphilic block copolymer with one hydrophilic end and one hydrophobic end on the basis of polyethylene glycol and an organic silicon oxygen ether monomer through substitution reaction and atom transfer radical polymerization (ATRP), and then enabling the amphiphilic block copolymer to be self-assembled and wrapped with an iodine-containing monomer (3-iodopropyl) trimethoxysilane in an aqueous solution to form nanoparticles; and finally, the iodine-containing nano particles with stable structures are formed by adjusting the pH (Potential of Hydrogen). The self-assembled nanoparticles prepared by the method disclosed by the invention have relatively uniform size distribution, and the iodine content and size of the nanoparticles can be regulated and controlled by regulating and controlling the ratio of the copolymer to the iodine-containing monomer in the assembling process. Meanwhile, the obtained series of iodine-containing nanoparticles have good CT imaging effect and biocompatibility, and have the potential of becoming a CT imaging contrast agent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biological detection, and in particular relates to CT visualization nanoparticles based on amphiphilic block copolymers, and a preparation method and application thereof. Background Art

[0002] Since Roentgen took the first X-ray, X-ray imaging has become an integral part of medical care. Computed tomography (CT) creates a three-dimensional image of the body by taking hundreds of X-ray images in multiple directions. It is used in various research and clinical settings as a non-invasive tissue imaging method. Its imaging principle is mainly through the detection of X-ray photons passing through the body, and the different absorption and scattering of photons by different tissues produce different degrees of X-ray attenuation. Compared with other medical imaging methods, CT imaging has the advantages of better display of calcification and bone lesions, short scanning time, clear images, clear anatomical relationships, and low price. However, the ability of this technology to distinguish soft tissues of similar density is limited, so it is necessary to improve the imaging effect by injecting contrast agents. Due to the high atomic number, high X-ray absorption coefficient, and its flexibility and functionality in chemical synthesis, iodine contrast media (ICM) have become the main category of CT contrast agents.

[0003] The development of ICM has experienced a transition from inorganic molecules to organic molecules, among which water-soluble sodium iodide and potassium iodide were the earliest ICMs used. However, when the concentration required for imaging is met, inorganic iodine solutions show high toxicity, which seriously hinders their clinical application. Subsequently, ICM developed in the direction of organic small molecules and achieved a transition from ionic to non-ionic, and from monomers to dimers. Currently, almost all commercially available and clinically approved ICMs are also organic small molecules.

[0004] However, existing organic small molecule ICMs still have a series of shortcomings such as severe nephrotoxicity, short circulation half-life, and easy to cause related immune responses. Therefore, there is an urgent need to develop the next generation of ICMs that can achieve long circulation, low toxicity and non-immunogenicity. Nanoparticle-type ICMs can reduce some of the problems of currently approved organic small molecule ICMs. One reason is that the low osmotic pressure of nanoparticles can reduce the risk of adverse reactions related to hyperosmosis during use; another reason is that nanoparticles with a particle size greater than 10nm can escape renal clearance, thereby showing a longer circulation time, and the modifiable / regulatory capabilities of nanoparticles provide sufficient development space for multimodal imaging, organ targeting, etc.

[0005] In summary, in order to further reduce the existing problems of ICM (nephrotoxicity, short circulation half-life, etc.), it is of great practical significance to develop a nanoparticle-type ICM with good biocompatibility and CT imaging effect. Summary of the invention

[0006] In order to overcome the deficiencies of the above-mentioned prior art, the present invention has developed a chemical synthesis method of an amphiphilic block copolymer based on polyethylene glycol and an organic silicone ether monomer, and the synthesized block copolymer is self-assembled in an aqueous solution and encapsulates an iodine-containing monomer to form nanoparticles, and then the pH is adjusted to achieve hydrolysis and cross-linking of the iodine-containing monomer and the hydrophobic segment of the copolymer, thereby achieving the stability of the colloidal structure. The prepared iodine-containing nanoparticles have good CT imaging effect and biocompatibility, and have broad application prospects.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is:

[0008] The first aspect of the present invention provides a method for preparing CT visualized nanoparticles based on amphiphilic block copolymers, the method comprising the following steps:

[0009] S1. Under an inert gas atmosphere, polyethylene glycol monomethyl ether, triethylamine and 2-bromoisobutyryl bromide are dissolved in an organic solvent, and reacted at room temperature for 40-60 hours. After the reaction, the compound 1 is obtained by washing, dialyzing and drying. The structural formula of the compound 1 is shown below:

[0010]

[0011] S2. Under anhydrous and oxygen-free conditions, compound 1 and 3-(methacryloyloxy)propyltrimethoxysilane are dissolved in an organic solvent, and copper bromide, pentamethyldiethylenetriamine (PMDETA) and cuprous bromide are added, and then condensation reflux reaction is carried out in an inert gas protection atmosphere. After the reaction, metal ions are removed, and compound 2 is obtained after washing. The structural formula of compound 2 is shown below:

[0012]

[0013] S3. Dissolve compound 2 and iodine-containing monomer (3-iodopropyl)trimethoxysilane in an organic solvent, add the mixture into water under stirring conditions, and obtain nanoparticles after dialysis.

[0014] Preferably, in S1, the average molecular weight of the polyethylene glycol monomethyl ether is 4000-8000.

[0015] Preferably, in S1, the molar ratio of polyethylene glycol monomethyl ether, triethylamine and 2-bromoisobutyryl bromide is 1:3-4:7-9.

[0016] Preferably, in S1, the concentrated reaction product is washed with cold ether, concentrated, dissolved in water, and dialyzed in a dialysis bag with a molecular weight cutoff of 700-2000 Da for 4-7 days.

[0017] Preferably, in S2, the temperature of the condensation reflux reaction is 60-80°C and the time is 20-30h.

[0018] Preferably, in S2, the organic solvent is a mixed system of tetrahydrofuran and ethanol in a volume ratio of 1:1.

[0019] Preferably, in S2, the usage ratio of the compound 1, 3-(methacryloyloxy)propyltrimethoxysilane, cupric bromide, pentamethyldiethylenetriamine and cuprous bromide is 350-400 mg: 500-550 μL: 0.4-0.7 mg: 20-30 μL: 10-20 mg.

[0020] Preferably, in S2, the reaction product is washed with anhydrous n-hexane, and then the remaining n-hexane is removed under vacuum.

[0021] Preferably, in S3, the stirring speed is 500rpm-1000rpm.

[0022] Preferably, in S3, the usage ratio of the compound 2 to the iodine-containing monomer is 68 mg: 10-200 μL.

[0023] Preferably, in S3, the dialysis is performed using a dialysis bag with a molecular weight cutoff of 700-1500Da for 20-30h, the pH of the dialysate is adjusted to 8-10, and then the dialysate is dialyzed for another 10-15h, and finally the dialyzate is performed using water for another 20-30h.

[0024] The second aspect of the present invention provides CT visualized nanoparticles based on amphiphilic block copolymers prepared by the preparation method described in the first aspect.

[0025] The third aspect of the present invention provides use of the CT visualization nanoparticles based on the amphiphilic block copolymer described in the second aspect in the preparation of a CT contrast agent.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] The invention discloses a method for preparing iodine-containing nanoparticles based on an amphiphilic block copolymer. First, a monohydroxyl-terminated polyethylene glycol and 2-bromoisobutyryl bromide are catalyzed by triethylamine to undergo a substitution reaction, and the reaction product is used as an initiator to polymerize 3-(methacryloyloxy)propyltrimethoxysilane containing a double bond through atom transfer radical polymerization (ATRP), thereby preparing an amphiphilic block copolymer with one end hydrophilic and the other end hydrophobic. Then, the amphiphilic block copolymer is self-assembled in an aqueous solution to encapsulate an iodine-containing monomer (3-iodopropyl)trimethoxysilane to form nanoparticles, and then the internal iodine-containing monomer and the polymer hydrophobic segment are hydrolyzed and condensed by adjusting the pH, and finally iodine-containing nanoparticles with stable structure are formed. The self-assembled nanoparticles prepared by the method of the invention have a relatively uniform size distribution, and the iodine content and size of the nanoparticles can be regulated by regulating the ratio of the copolymer and the iodine-containing monomer during the assembly process. At the same time, the obtained series of iodine-containing nanoparticles have good CT imaging effect and biocompatibility, and have the potential to become CT imaging contrast agents. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is the H NMR spectrum of compound 1 generated by the substitution reaction of polyethylene glycol monomethyl ether and 2-bromoisobutyryl bromide;

[0029] Figure 2 The H NMR spectrum of the block copolymer (Compound 2) obtained by polymerizing 3-(methacryloyloxy)propyltrimethoxysilane using Compound 1 as an initiator;

[0030] Figure 3 A synthetic route for preparing iodine-containing nanoparticles by self-assembly of compound 2 and iodine-containing monomers (where n=113, m=28);

[0031] Figure 4 This is the particle size distribution diagram of the iodine-containing nanoparticles obtained in Example 1;

[0032] Figure 5 This is a particle size distribution diagram of iodine-containing nanoparticles obtained in Example 2;

[0033] Figure 6 This is the particle size distribution diagram of the iodine-containing nanoparticles obtained in Example 3;

[0034] Figure 7 This is the particle size distribution diagram of the iodine-containing nanoparticles obtained in Example 4;

[0035] Figure 8 This is the particle size distribution diagram of the iodine-containing nanoparticles obtained in Example 5;

[0036] Fig. 9 This is a transmission electron microscope image of the iodine-containing nanoparticles obtained in Example 4;

[0037] Fig.10 CT images of the iodine-containing nanoparticles obtained in Example 1-5;

[0038] Fig.11 The relationship curve between the CT value and the concentration of the iodine-containing nanoparticles obtained in Examples 1-5;

[0039] Fig.12 This is a diagram for evaluating the cytotoxicity of the iodine-containing nanoparticles obtained in Example 2 at different concentrations (MRC-5 cell line, 24 h);

[0040] Fig.13 This is a diagram for evaluating the cytotoxicity of the iodine-containing nanoparticles obtained in Example 3 at different concentrations (MRC-5 cell line, 24 h);

[0041] Fig.14 This is a diagram for evaluating the cytotoxicity of the iodine-containing nanoparticles obtained in Example 4 at different concentrations (MRC-5 cell line, 24 h);

[0042] Fig.15 This is a diagram for evaluating the cytotoxicity of the iodine-containing nanoparticles obtained in Example 5 at different concentrations (MRC-5 cell line, 24 h). DETAILED DESCRIPTION

[0043] The specific embodiments of the present invention are further described below. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0044] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are commercially available unless otherwise specified.

[0045] Examples 1-5: Preparation of iodine-containing nanoparticles based on amphiphilic block copolymers

[0046] (1) Synthesis of Compound 1:

[0047] Under argon protection atmosphere at 0°C, 5 g of polyethylene glycol monomethyl ether (average molecular weight of 5000, 1 mmol) and 515 μL of triethylamine (3.71 mmol) were added to 30 mL of anhydrous dichloromethane and stirred for 10 min. Separately, 1840 g of 2-bromoisobutyryl bromide (8 mmol) was dissolved in 10 mL of anhydrous dichloromethane and then dropped into the above mixed system, and then reacted at room temperature for 48 h under argon protection. After stopping the reaction, the system was concentrated under reduced pressure to 5-10 mL, and the concentrated system was dripped dropwise into cold ether (the volume ratio of the concentrated system to ether was about 1:15-1:20), washed three times with cold ether, and a vacuum pump was connected to remove a small amount of residual ether, and the obtained solid was dissolved with an appropriate amount of deionized water (solid-liquid ratio was about 5g / 100mL-200mL), placed in a dialysis bag with a molecular weight cutoff of 1000Da and dialyzed for 5 days, and finally freeze-dried to obtain a pure white solid, whose nuclear magnetic resonance hydrogen spectrum is as follows: Figure 1 The synthesis route of this step is as follows:

[0048]

[0049] Wherein, n=113.

[0050] (2) Synthesis of Compound 2:

[0051] In the absence of water and oxygen, 379 mg of compound 1 (0.0729 mmol) and 520 μL of 3-(methacryloyloxy)propyltrimethoxysilane (2.1865 mmol) were added to a mixture of 10 mL of tetrahydrofuran and 10 mL of anhydrous ethanol. After stirring for 10 min, 0.5 mg of copper bromide, 25 μL of pentamethyldiethylenetriamine (PMDETA) and 15 mg of cuprous bromide were added in sequence. Then, the mixture was condensed and refluxed at 70 ° C for 24 h in an argon atmosphere. After the reaction, the argon was removed to allow the system to contact oxygen to terminate the reaction. Finally, the metal ions were removed by alkaline alumina, and the system was concentrated under reduced pressure until it was about one-fourth of the original volume. The system was dripped into anhydrous n-hexane (the volume ratio of the concentrated system to n-hexane was about 1:15-1:20), washed three times with anhydrous n-hexane, and a vacuum pump was connected to remove the remaining n-hexane to obtain a white solid, which was compound 2. Its nuclear magnetic resonance hydrogen spectrum was as follows: Figure 2 The synthesis route of this step is as follows:

[0052]

[0053] Wherein, n=113, m=28.

[0054] (3) Preparation of iodine-containing nanoparticles by self-assembly:

[0055] Weigh 68 mg of compound 2 and different volumes of iodine-containing monomer (3-iodopropyl) trimethoxysilane (specific ratios are shown in Table 1) and dissolve them in 1 mL of tetrahydrofuran, then slowly add them dropwise to 6 mL of deionized water under high-speed stirring (500 rpm-1000 rpm), continue stirring for 2 hours after the addition, and place them in a dialysis bag with a molecular weight cutoff of 1000 Da and dialyze them with pure water for 24 hours, then replace the dialysate, and add ammonia water to the external dialysate (i.e., the newly replaced pure water) to adjust the pH to about 9, continue dialysis for 12 hours, and then switch to deionized water for another 24 hours to obtain 5 different nanoparticles. The synthetic route of this step is as follows Figure 3 shown.

[0056] Table 1 Sample composition of Examples 1-5 and particle size and Zeta potential of the formed nanoparticles

[0057]

[0058] Experimental example: Characterization and performance testing of iodine-containing nanoparticles based on amphiphilic block copolymers

[0059] (1) Particle size characterization:

[0060] The hydrated particle size of the five self-assembled iodine-containing nanoparticles (specific ratios and compositions are shown in Table 1) in the embodiment was measured using a nanoparticle size and zeta potential analyzer. The results are shown in Table 1 and Figure 4-8 As shown, it can be seen that each group of nanoparticles has a relatively uniform size distribution, and as the proportion of iodine-containing monomers increases, the particle size of the nanoparticles gradually increases, and the Zeta potential of each group is roughly between -2.5mV and -4.5mV. Fig. 9 ) It can be seen that the nanoparticles are spherical and most of the particle sizes are between 16-24 nm, which is similar to the dynamic light scattering (DLS) particle size measurement results.

[0061] (2) Characterization of CT imaging effects:

[0062] The iodine-containing nanoparticle solutions of Examples 1-5 were freeze-dried and reconfigured into aqueous solutions of different mass concentrations (1 mg / mL, 2 mg / mL, 4 mg / mL, 8 mg / mL, 16 mg / mL, 32 mg / mL, and 64 mg / mL) using deionized water. The solutions were then transferred to a 96-well plate (150 μL per well) and scanned using a CT scanner. The generated data files were processed and analyzed using RadiAntDICOM Viewer. The obtained CT images are shown in FIG. Fig.10 In addition, a scatter plot was drawn based on the measured CT value and a fitting curve was drawn (see Fig.11). It can be seen that except for Example 1, the CT imaging effect of other groups becomes gradually more obvious as the concentration increases; for the same mass concentration, the CT imaging effect becomes more and more significant due to the increase in the proportion of iodine-containing monomers from Example 1 to Example 5.

[0063] (3) Cytotoxicity characterization:

[0064] The MRC-5 cell line (purchased from CytoKind) was used to characterize the cytotoxicity of four groups of nanoparticles in Examples 2 to 5 by the CCK-8 method (Example 1 was not characterized due to the lack of CT imaging effect). About 5000 cells were plated in each well of a 96-well plate, and the cells were incubated with nanoparticles of different concentrations (the final concentration of the nanoparticles was 50 μg / mL-1 mg / mL) for 24 hours. After removing the supernatant, 10 μL of CCK-8 reagent and 90 μL of DMEM culture medium were added to each well and incubated for 1.5 hours. Finally, the relative viability of the cells was measured by an ELISA instrument (calculated by the absorbance at 450 nm). The results are shown in FIG. Figure 12-15 As shown, it can be seen that the cell compatibility of each group showed a certain concentration dependence. At the same time, within the set concentration range (50 μg / mL-1 mg / mL), the cell viability was higher than 80%, proving that the material has good cell compatibility.

[0065] In summary, the present invention synthesizes an amphiphilic block copolymer with one end hydrophilic and the other end hydrophobic based on polyethylene glycol and organic silicone ether monomers, and then uses the copolymer to self-assemble and encapsulate iodine-containing monomers to form nanoparticles, which are combined with pH adjustment to form nanocolloids with stable structure and high X-ray opacity. The nanoparticles have good CT imaging effect and biocompatibility, and have the potential to become CT imaging contrast agents.

[0066] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the protection scope of the present invention.

Claims

1. A method for preparing CT visualized nanoparticles based on amphiphilic block copolymers, characterized in that: The following steps are involved: S1. Under an inert gas atmosphere, polyethylene glycol monomethyl ether, triethylamine and 2-bromoisobutyryl bromide are dissolved in an organic solvent, and reacted at room temperature for 40-60 hours. After the reaction, the compound 1 is obtained by washing, dialyzing and drying. The structural formula of the compound 1 is shown below: Wherein, n = 110-120; S2. Under anhydrous and oxygen-free conditions, compound 1 and 3-(methacryloyloxy)propyltrimethoxysilane are dissolved in an organic solvent, and copper bromide, pentamethyldiethylenetriamine (PMDETA) and cuprous bromide are added, and then condensation reflux reaction is carried out in an inert gas protection atmosphere. After the reaction, metal ions are removed, and compound 2 is obtained after washing. The structural formula of compound 2 is shown below: Wherein, n=110-120, m=20-30; S3. Dissolve compound 2 and iodine-containing monomer (3-iodopropyl)trimethoxysilane in an organic solvent, add the mixture into water under stirring conditions, and obtain nanoparticles after dialysis.

2. The method for preparing CT visualized nanoparticles based on amphiphilic block copolymers according to claim 1, characterized in that: In S1, the average molecular weight of the polyethylene glycol monomethyl ether is 4000-8000.

3. The method for preparing CT visualized nanoparticles based on amphiphilic block copolymers according to claim 1, characterized in that: In S1, the molar ratio of polyethylene glycol monomethyl ether, triethylamine and 2-bromoisobutyryl bromide is 1:3-4:7-9.

4. The method for preparing CT visualized nanoparticles based on amphiphilic block copolymers according to claim 1, characterized in that: In S2, the temperature of the condensation reflux reaction is 60-80°C and the time is 20-30h.

5. The method for preparing CT visualized nanoparticles based on amphiphilic block copolymers according to claim 1, characterized in that: In S2, the organic solvent is a mixed system of tetrahydrofuran and ethanol in a volume ratio of 1:

1.

6. The method for preparing CT visualized nanoparticles based on amphiphilic block copolymers according to claim 1, characterized in that: In S2, the usage ratio of the compound 1, 3-(methacryloyloxy)propyltrimethoxysilane, cupric bromide, pentamethyldiethylenetriamine and cuprous bromide is 350-400 mg: 500-550 μL: 0.4-0.7 mg: 20-30 μL: 10-20 mg.

7. The method for preparing CT visualized nanoparticles based on amphiphilic block copolymers according to claim 1, characterized in that: In S3, the usage ratio of the compound 2 to the iodine-containing monomer is 68 mg: 10-200 μL.

8. The method for preparing CT visualized nanoparticles based on amphiphilic block copolymers according to claim 1, characterized in that: In S3, the dialysis is performed by first dialysis for 20-30 hours using a dialysis bag with a molecular weight cutoff of 700-1500Da, then dialyzing for another 10-15 hours after adjusting the pH of the dialysate to 8-10, and finally dialyzing for another 20-30 hours using water.

9. CT visualized nanoparticles based on amphiphilic block copolymers prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the CT visualization nanoparticles based on the amphiphilic block copolymer according to claim 9 in the preparation of CT contrast agents.

Citation Information

Patent Citations

  • Anticoagulation coating and preparation method and application thereof

    CN102321419A

  • Janus nano-particles based on block copolymer and preparation method thereof

    CN106317415A

  • Coating agent, coated film, and manufacturing method of coated film

    JP2021080461A